Morphological characters, pharmacognostical parameters, and preliminary phytochemical screening of Curcuma sahuynhensis Škorni?k. & N.S.Lý in Quang Ngai Province, Vietnam - TRAN VAN CHEN; DUONG NGUYEN XUAN LAM; CAO LY TAN THONG; DANH DUC NGUYEN; NGUYEN THANH TO NHI; NGUYEN THANH TRIET (Society for Indonesian Biodiversity, 2022)
Abstract. Chen TV, Lam DNX, Thong CLT, Nguyen DD, Nhi NTT, Triet NT. 2022. Morphological characters, pharmacognostical parameters, and preliminary phytochemical screening of Curcuma sahuynhensis Škorni?k. & N.S.Lý in Quang Ngai Province, Vietnam. Biodiversitas 23: 3907-3920. Curcuma sahuynhensis (Vegetable Turmeric or Rau Nghe) has been used as a flavor and a spice in Vietnamese cuisines. Information on micromorphological characters, pharmacognostic parameters, and phytochemical screening of C. sahuynhensis has not been reported in the literature. Therefore, the accurate verification of plants requires further research to determine their quality and safety in order to make optimal use of them as raw materials for medicines and food. In this work, macro-and micromorphological features, pharmacognostic parameters, and phytochemical screening were performed according to the Vietnamese Pharmacopoeia V guidelines and other published data. Macromorphologically, it can grow up to 75 ± 5 cm tall and up to 10 per pseudostem. The inflorescence consists of 10–24 bracts. Rhizome branched, and remote tubers were present. The flower was yellow with a warm yellow midrib band, and an incision up to 0.6 cm long on the apex labellum. Anthers are L-shaped, stalked with no knobs below the thecae. Micromorphologically, there are anatomical similarities between the species in the genus Curcuma, particularly in terms of leaves, roots, and rhizomes. Under the lower epidermis of the leaf midrib are small vascular bundles (8–10 bundles). The stomatal index (SI) was 8.97 in abaxial and 1.06 in adaxial of the leaf. Prismatic calcium oxalate crystals were found in the leaf but they were absent in the root. Starch grains were also found in leaf powder (11–12.5 µm) and rhizome powder (15–20 µm). Additionally, the presence of oleoresin (in leaves and rhizomes) and the absence of crystals in the cortex region of the rhizome was found to be significant features in identifying C. sahuynhensis. Phytochemical screening found that its rhizome and inflorescence contain essential oil, amino acids, flavonoids, tannins, coumarins, triterpenoids, polyuronides, and reducing compounds. Pharmacognostically, rhizome powders' moisture content, total ash value, and acid-insoluble ash value were 11.79 ± 0.20%, 7.32 ± 0.60%, and 0.24 ± 0.08%, respectively.